2019
DOI: 10.1111/jse.12471
|View full text |Cite
|
Sign up to set email alerts
|

Cytotaxonomy and geographic distribution of cytotypes of species of the South American genus Chrysolaena (Vernonieae, Asteraceae)

Abstract: Understanding speciation and biodiversity patterns in plants requires knowledge of the general role of climate in allowing polyploids to escape competition and persist with their diploid progenitors. This is a particularly interesting issue in widespread species that present multiple ploidy levels and occur across a heterogeneous environment. Chrysolaena (Vernonieae, Asteraceae) is a cytogenetically very diverse genus, with significant interspecific and intraspecific ploidy level variation and with continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Cytogeographic patterns may reveal significant amounts of diversity by identifying multiple chromosomal races among related species or within a single taxonomic species and, therefore, contribute to the conservation of rare species and ecological restoration ( Soltis et al, 2007 ; do Pico et al, 2019 ). The cytogeographic data obtained allowed us to find a clear distribution pattern, since the two most frequent cytotypes, II and IV, occupy different areas and do not co-exist in the same area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytogeographic patterns may reveal significant amounts of diversity by identifying multiple chromosomal races among related species or within a single taxonomic species and, therefore, contribute to the conservation of rare species and ecological restoration ( Soltis et al, 2007 ; do Pico et al, 2019 ). The cytogeographic data obtained allowed us to find a clear distribution pattern, since the two most frequent cytotypes, II and IV, occupy different areas and do not co-exist in the same area.…”
Section: Discussionmentioning
confidence: 99%
“…Variations of karyotype and chromosome number, such as polyploidy and aneuploidy, can drive genomic novelty and intraspecific diversification and act as a mode of immediate and sympatric species ( Soltis et al, 2015 ; do Pico et al, 2019 ). Unrecognized cytotype variation can lead to an underestimation of species richness ( Soltis et al, 2007 , 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Polyploids have also been hypothesized to be better adapted to harsh environments than diploids (Hagerup 1931). Comparisons between diploids and natural or synthetic polyploids have shown that polyploids are more tolerant to water deficit Maherali et al 2009;Deng et al 2012;Hao et al 2013), salinity (Chao et al 2013), environments that are xeric (Ramsey 2011), extremely cold Brochmann et al 2004;Deng et al 2012) or extremely hot (Zhang et al 2010;Thompson et al 2014), have wider geographic ranges (Tuler et al 2019;Via do Pico et al 2019) and greater ecological plasticity and invasiveness (Rejlová et al 2019). Polyploidy can also lead to flower morphological differentiation and alter plant-pollinator interactions (e.g., .…”
Section: Introductionmentioning
confidence: 99%